1995
DOI: 10.1063/1.871318
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopy of hot solid density plasmas produced by subpicosecond high contrast laser pulses at 1018–1019 W/cm2

Abstract: Analysis is presented of K-shell spectra obtained from solid density plasmas produced by a high contrast (1O":l) subpicosecond laser pulse (0.5 pm) at 10'8-10'9 W/cm'. Stark broadening measurements of He-like and Li-like lines are used to infer the mean electron density at which emission takes place. The measurements indicate that there is an optimum condition to produce x-ray emission at solid density for a given isoelectronic sequence, and that the window of optimum conditions to obtain simultaneously the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 60 publications
0
66
0
Order By: Relevance
“…The latter experiments have been performed using green light of approximately the same pulse duration with laser intensities up to 4 × 10 18 W/cm 2 and 10 19 W/cm 2 , correspondingly. However, the penetration depth of hot electrons in [24] was more than two orders of magnitude longer than in [25]. Two possible disparate scenarios may explain these controversies in high-energy electron and ion generation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The latter experiments have been performed using green light of approximately the same pulse duration with laser intensities up to 4 × 10 18 W/cm 2 and 10 19 W/cm 2 , correspondingly. However, the penetration depth of hot electrons in [24] was more than two orders of magnitude longer than in [25]. Two possible disparate scenarios may explain these controversies in high-energy electron and ion generation.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, in [27], which models the transport of fast electrons generated by a 20-J laser, it was shown that only 0.6 J are required to ionize a target of 250-µm thickness. Note that the experiment in [24] was performed with an order of magnitude higher laser energy (and so larger prepulse energy) than the experiment in [25], which displayed a dramatic difference in the hot-electron penetration depths. The aim here is to see how both underdense preplasma scale length and solid dense plasma thickness determine the efficiency of ion generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…electronic satellites. Time duration of these kilovolt emissions have been studied with a sub-ps resolution streak camera [77,78], and conversion efficiencies have been determined for more energetic x-rays [79]. Spectroscopy of ultrafast plasmas has been performed with contrast-clean laser pulses obtained through frequency doubling [80,81] and tamped Al-tracer layer-targets [82].…”
Section: Helium-like Lines and Satellitesmentioning
confidence: 99%
“…Temperatures between 200 and 2000 eV in solid targets have been reported in a variety of experiments. [4][5][6][7][8][9][10][11][12] Heating of buried Al layers and the effect of a nanosecond pedestal ahead of the main laser pulse have been recently discussed by Evans et al 13 Measurements of density and temperature of hot dense plasmas have been often inferred from spectroscopic techniques, namely intensity ratios [3][4][5][6][7][8][9][10][11][12] and wavelength shifts 14 of Lyman and Balmer series lines. Use of only line shapes is not sufficient due to the complexity of atomic radiation transport and absorption within the target, thus it becomes important to infer information using radiation-hydrodynamics, particle-incell ͑PIC͒, and collisional radiative atomic codes.…”
Section: Introductionmentioning
confidence: 99%